Ongoing research on seismic safety assessment - Raimundo Delgado (2007)
Research on seismic safety assessment has been the centre of great interest among the scientific community inrecent years. Although the devastating impact of earthquakes on current society should be incentive enough toincrease research on seismic safety assessment, the development of more realistic nonlinear mechanicalbehaviour models and the continuously increasing computation capabilities are paramount factors contributing agreat deal to the increase of such interest.The paper will present some of the current trends of scientific research on seismic safety assessment,emphasizing the work currently being developed at FEUP on this domain. The paper will mainly focus studiesaddressing the seismic behaviour of structures and also different types of methodologies for seismic safetyassessment, ranging from more simplified to more complex methods.Reference will also be made to experimental research being currently carried out at FEUP and will serve assupport for the development of numerical models simulating the effects of different seismic strengtheningtechniques.